2002
DOI: 10.1287/mksc.21.2.178.148
|View full text |Cite
|
Sign up to set email alerts
|

Close Encounters of Two Kinds: False Alarms and Dashed Hopes

Abstract: People are frequently exposed to potentially attractive events that are subsequently and unexpectedly reversed and to potentially painful events, which are also unexpectedly reversed. In the process of being returned to the initial asset position, does the sequence in which the positive and negative events occur matter? This issue of the combined effect of pleasurable and painful stimuli has received scant theoretical or empirical attention. We attempt to fill this lacuna in the literature by studying the retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 27 publications
3
43
0
1
Order By: Relevance
“…There are a very few studies testing the dynamic aspects of prospect theory using US subjects. Chen and Rao (2002) found that the order in which two opposite events (gain/loss) occurred affected the subject's final affective state, suggesting that a shift in the reference point occurred after the first event. Gneezy (2005) assumed that subjects are most willing to sell when the current price is equal to the reference point, and showed that assuming a stock's peak price to be the reference point best explained subjects' willingness to sell that stock.…”
Section: Reference Point Adaptation In Prospect Theorymentioning
confidence: 98%
“…There are a very few studies testing the dynamic aspects of prospect theory using US subjects. Chen and Rao (2002) found that the order in which two opposite events (gain/loss) occurred affected the subject's final affective state, suggesting that a shift in the reference point occurred after the first event. Gneezy (2005) assumed that subjects are most willing to sell when the current price is equal to the reference point, and showed that assuming a stock's peak price to be the reference point best explained subjects' willingness to sell that stock.…”
Section: Reference Point Adaptation In Prospect Theorymentioning
confidence: 98%
“…Investors may eventually update their reference points to the current price or partially update to a price between the initial price and the current price. Chen and Rao (2002) suggest that people's reference points shift after a stimulus is presented, but do so incompletely. However Chen and Rao (2002) only examined situations in which two outcomes occur with one being positive and the other being negative.…”
Section: The Reference Point In Prospect Theorymentioning
confidence: 99%
“…Chen and Rao (2002) suggest that people's reference points shift after a stimulus is presented, but do so incompletely. However Chen and Rao (2002) only examined situations in which two outcomes occur with one being positive and the other being negative. Gneezy (2002) inferred reference point adaptation from participants' decisions to sell their stocks when stock prices followed a random walk.…”
Section: The Reference Point In Prospect Theorymentioning
confidence: 99%
“…In addition, the adaptation of reference point is a huge issue. As Chen and Rao (2002) highlighted in their experiments, although people's reference points shift immediately after a stimulus occurs, such a shift is incomplete. The magnitude of the shift depends on the time difference between two stimuli.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 96%